Hydrogen production via direct core-shell conjugation of functionalized fullerenes and ZnO QDs with accelerated optical catalytic properties - Juhee You; Dan Na; Yuwen Wei; Hyunjin Cho; Seok-Ho Seo; Young Jae Park; Dong Gwon Heo; Sang-Youp Yim; Seunghwan Kim; Soohyung Park; In Seok Seo; Mehmet Suha Yazici; et al. (Chemical Engineering Journal, 2026)

Size‐, sex‐ and site‐dependent morphological variation in the stone flounder ( Kareius bicoloratus ) from Korean coastal waters - Eun Jeong Kim; Songhyun Gwon; Ju Hwan Park; In Chul Bang; Yoon Kwon Nam (Journal of Fish Biology, 2026)
Kareius bicoloratus is a commercially important flatfish in Korean coastal fisheries and an ecologically relevant benthic species in nearshore ecosystems. To evaluate how multiple biological and environmental factors jointly shape flatfish morphology, we analysed 81 morphometric indices and two‐dimensional geometric morphometrics (GMM) in wild K. bicoloratus collected from two Korean coastal regions, incorporating size, sex and sampling site. Classical morphometrics based on a three‐way ANOVA framework identified body size and sex as the primary drivers of shape variation, particularly influencing surface area‐, depth‐ and angular traits, whereas geographic effects were more limited and context dependent. GMM analyses supported these patterns. Procrustes ANOVA detected significant shape effects of size, sex and site, and CVA revealed clear multivariate separation among groups, with Mahalanobis distances of 3.28–5.49 among sex groups and Procrustes distances of 0.032–0.049. Geographic divergence was also evident in GMM space, with Procrustes distances of 0.033–0.036 between sites. Allometry analyses indicated heterogeneous allometric trajectories for size and sex but not for site. Mitochondrial DNA analyses revealed moderate genetic differentiation between regions, and Mantel tests detected a weak but significant association between genetic and morphological distances. These findings provide a robust morphological baseline for K. bicoloratus .

Chemical constituents of culture broth of the marine-derived fungus Towyspora aestuari and their antioxidant activity - Mungyeong Gwon; Dae-Won Ki; Dae-Cheol Choi; Ji-Yul Kim; Won-Gi Seo; Yongkuk Lee; In-Kyoung Lee; Bong-Sik Yun (Phytochemistry Letters, 2025)

Enhancement of renal fibrosis in PHF20 transgenic mice - Uijin Juang; Soohyeon Lee; Suhwan Gwon; Woohyeong Jung; Huonggiang Nguyen; Qingzhi Huang; Beomwoo Lee; So Hee Kwon; Seon-Hwan Kim; In Soo Kim; Jongsun Park (Toxicological Research, 2025)

Imbalance of sediment transport in a meso-tidal bay: effect of tidal pumping and residual circulation - Su In Kim; Jun Young Seo; Jae-Hun Park; Pyeong Joong Kim; In Gwon Kim; Kyung Man Kim; Ho Kyung Ha (Frontiers in Marine Science, 2024)
In-situ mooring systems with acoustic Doppler current profilers were installed in the western (TM01) and eastern (TM02) parts of Yeosu Bay from September 3 to October 2, 2021, to understand the controlling mechanisms of suspended sediment transport. In the bay, freshwater from the Seomjin River freely exchanges with seawater from the open sea. Over the mooring period, current flows were mainly dominated by ebb tides. Power spectral density analysis of the suspended sediment concentration (SSC) exhibited a quarter-diurnal (6.21 h) frequency at TM01 and a semi-diurnal (12.42 h) frequency at TM02. The results suggested that SSC variations in the western part were driven primarily by local sediment resuspension, while they were influenced predominantly by horizontal advection in the eastern part. Differences in SSC variation at the two stations could be due to the physical properties of the bed sediments (TM01: sandy mud containing shell fragments, TM02: mud). Such current flows and SSC variations over the tidal cycles caused an imbalance of sediment transport. At TM01, the sediment fluxes were dominantly seaward due to tidal pumping (88% of the total) and the discharge of suspended sediments in the surface layer by residual circulation. At TM02, landward sediment fluxes were driven primarily by the residual current (73% of the total). Although the suspended sediment fluxes tended to be compensated and balanced mutually by circulation over the entire period, the suspended sediment fluxes at TM02 were approximately twice higher than those at TM01. This was caused by the difference in SSC asymmetry between flood and ebb at the two stations. The mechanisms controlling the transport of suspended sediment could vary spatially, and the relative contribution of tidal pumping and residual circulation could result in an imbalance of sediment transport.

Implantable electrical stimulation bioreactor with liquid crystal polymer-based electrodes for enhanced bone regeneration at mandibular large defects in rabbit - Chaebin Kim; Hoon Joo Yang; Tae Hyung Cho; Beom Seok Lee; Tae Mok Gwon; Soowon Shin; In Sook Kim; Sung June Kim; Soon Jung Hwang (Medical & Biological Engineering & Computing, 2020)

Mesenchymal signaling in dorsoventral differentiation of palatal epithelium - Wern-Joo Sohn; Gi-Jeong Gwon; Hyeng-Soo Kim; Sanjiv Neupane; Sung-Jin Cho; Jae-Hyung Lee; Hitoshi Yamamoto; Je-Yong Choi; Chang-Hyeon An; Youngkyun Lee; Hong-In Shin; Sanggyu Lee; et al. (Cell and Tissue Research, 2015)

The role of APCDD1 in epithelial rearrangement in tooth morphogenesis - Sanjiv Neupane; Wern-Joo Sohn; Gi-Jeong Gwon; Ki-Rim Kim; Sanggyu Lee; Chang-Hyeon An; Jo-Young Suh; Hong-In Shin; Hitoshi Yamamoto; Sung-Won Cho; Youngkyun Lee; Jae-Young Kim (Histochemistry and Cell Biology, 2015)

Reciprocal interactions of Fgf10/Fgfr2b modulate the mouse tongue epithelial differentiation - Wern-Joo Sohn; Hye-In Jung; Min-A Choi; Jin-Hyun Han; Gi-Jeong Gwon; Hitoshi Yamamoto; Sanggyu Lee; Zae Young Ryoo; Eui-Kyun Park; Hong-In Shin; Han-Sung Jung; Jae-Young Kim (Cell and Tissue Research, 2011)

Inhibitory effect of immature plum on PMA-induced MMP-9 expression in human hepatocellular carcinoma - Mi Hee Yu; Hyo Gwon Im; Sung Gyu Lee; Dae-Ik Kim; Hwa Jeong Seo; In-Seon Lee (Natural Product Research, 2009)

Effects of ethanol extract from Saururus chinensis (Bour.) Baill on lipid and antioxidant metabolisms in rats fed a high-fat diet - Mi Hee Yu; Hyo Gwon Im; Ji-Won Lee; Mi-Hyang Hwang Bo; Hyun-Jeong Kim; Suk Kyung Kim; Shin Kyo Chung; In-Seon Lee (Natural Product Research, 2008)

Changes in retinal neuronal populations in the DBA/2J mouse - Jung-Il Moon; In-Beom Kim; Jae-Sung Gwon; Myoung-Hee Park; Tae-Hoon Kang; Eun-Jin Lim; Kyu-Ryong Choi; Myung-Hoon Chun (Cell and Tissue Research, 2005)